Prolonged care delivery time and reduced rate of electrophysiological procedures during the lockdown period due to Covid-19 outbreak. (4th May 2021) - Menichetti, Francesca; Nesti, Martina; Notarstefano, Pasquale; Fazi, Antonio; Del Rosso, Attilio; Solarino, Gianluca; La Pira, Federica; Giorgi, Davide; Arena, Giuseppe; Rossi, Andrea; Segreti, Luca; Piacenti, Marcello; et al.
ABSTRACT: Objectives: The aim of this study is to demonstrate how Electrophysiology activity has been impacted by the pandemic Coronavirus disease 2019 (COVID-19). Methods: In this multicenter retrospective study, we analyze all consecutive patients admitted for electrophysiological procedures during the COVID-19 lockdown in the Tuscany region of Italy, comparing them to patients hospitalized in the corresponding period of the previous year. Results: The impact of COVID-19 on cardiac arrhythmia management was impressive, with a reduction of more than 50% in all kinds of procedures. A gender gap was observed, with a more relevant reduction for female patients. Arrhythmic urgencies requiring a device implant showed a reduced time from symptoms to first medical contact but the time from first medical contact to procedure was significantly prolonged. Conclusion: Hospitals need to consider how outbreaks may affect health systems beyond the immediate infection. Routine activity should be based on a risk assessment between the prompt performance of procedure and its postponement. Retrospective observational analysis such as this study could be decisive in evidence-based medicine of any future pathogen outbreak. Nonstandard Abbreviations and Acronyms PM= pacemakerICD= implantable cardioverter defibrillatorECV= electrical cardioversionEPS= electrophysiological studyAP= ablations proceduresCIED= cardiac implantable electronic devicesWCD= wearable cardioverter defibrillatorEP Lab= Electrophysiology LaboratoriesAVNRT =atrioventricular nodal reentry tachycardiaAVRT= atrioventricular reentry tachycardiaAFL= atrial flutterAF= atrial fibrillationVT= ventricular tachycardiaAT= atrial tachycardia